Estimation of the parameters of a poisson rectangular distribution - Bhattacharya, S. K.; Holla, M. S. (Defence Science Journal, 2014)
The application of Poisson-Rectangular distribution in an industrial sampling problem, when the process mean is subjected to fluctuations, is indicated. Moment estimators of the parameters involved are discussed in detail. A problem of misclassification in the inspection of defects on finished articles and manufactured products is also included.